PENGARUH ASPEK NON-KOGNITIF SELF REGULATION LEARNING TERHADAP KEBERHASILAN AKADEMIK MAHASISWA PADA MATA KULIAH BUDI PEKERTI DAN KARAKTER - Agung Kesna Mahatmaharti; Diah Puji Nali Brata (STKIP PGRI Jombang, 2021)
One of the means to create quality human resources is education. This requires educational institutions to produce quality resources. Quality education can at the same time create superior human resources. Educators are one of the human components in the learning process whose role is to form potential and quality human resources. The ideal learning paradigm today is student-centered learning oriented. Students are given the freedom to construct their own knowledge and are actively involved in finding various learning information. Learners as objects as well as subjects of learning. Active involvement of students in the learning process can create fun learning. This study aims to describe the non-cognitive factors that affect the performance and success of students, the influence on performance and academic success. Using a quantitative descriptive approach that explains the influence of non-cognitive aspects of self-regulation learning on students' academic success in the Budi Pekerti and Character courses. The research was carried out at the PPKN STKIP PGRI Jombang Study Program. The subjects in this study were PPKN students batch 2020. The subjects used in this study were 16 students using the population sample technique. The research instrument used a questionnaire and documentation. Analysis of quantitative data used in this study using statistical tests with simple linear regression test. Data analysis using SPSS 21. Significant value <0.05 then Ho is rejected and Ha is accepted. The results of the analysis show that the significance value of = 0.000 then 0.000 <0.05 therefore Ho is rejected so that there is an influence of the X variable on the Y variable. Thus it can be said that the non-cognitive aspect of self-regulation learning affects the academic success of students in the Budi Pekerti course. and Character. According to the analysis, it was obtained that X = 0.912 and Y = 0.912 > 0.5, indicating a strong correlation between X and Y. According to the Summary Model as much as 91.2% of the Y variable is influenced by the X variable, so 100% - 91.2% the remaining 8.8% means that the remainder shows the influence of other factors